Problems and Prospects of Urbanization in Kathmandu Valley - Singh, Ramesh Prasad; Dhakal, Januka (International Journal of Atharva, 2024)
The capital of Nepal, Kathmandu, is undergoing rapid urbanization with issues like overcrowding, infrastructure strain, and environmental challenges. Informal settlements highlight resource disparities. The study explores urbanization's impact on cultural identity and social dynamics. Effective governance is crucial for managing urbanization and promoting social inclusion, but Nepal faces challenges like slow law implementation and corruption. Governance is pivotal for development, addressing issues like corruption and law enforcement. Despite challenges, urbanization presents opportunities for new industries and social services. The study aims to identify prospects for sustainable urbanization in Kathmandu, emphasizing green infrastructure, sustainable transportation, and community-based initiatives. A sociological perspective aids in understanding social dynamics and potential opportunities arising from urban growth.